2017
DOI: 10.1111/ijac.12649
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the electromechanical material properties of a multilayer ceramic capacitor

Abstract: A multilayer ceramic capacitor (MLCC) vibrates when an electrical signal containing an alternating current (AC) component is applied to it. The piezoelectric and electrostrictive coefficients of the dielectric layer are needed to analyze such vibrations because both affect the vibration. Also, they must be determined for various direct current (DC) biases because an MLCC is operated with various electrical signals and the coefficients vary as the DC bias changes. We determined the coefficients by measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…accepted superior electronic insulation and ultrahigh shear modulus (55.1 GPa) of LiF. [23] It is worth mentioning that the F 1s spectra and S 2p spectra of NSEI are much stronger than that in CSEI, which proved that the porous structure of COF conduced to separate lithium metal from TFSI − and avoided side reactions ( Figure S20, Supporting Information). What's more, much less TFSI − ions decomposed on the surface of COF-Li, because they decomposed more thoroughly meanwhile.…”
Section: Resultsmentioning
confidence: 99%
“…accepted superior electronic insulation and ultrahigh shear modulus (55.1 GPa) of LiF. [23] It is worth mentioning that the F 1s spectra and S 2p spectra of NSEI are much stronger than that in CSEI, which proved that the porous structure of COF conduced to separate lithium metal from TFSI − and avoided side reactions ( Figure S20, Supporting Information). What's more, much less TFSI − ions decomposed on the surface of COF-Li, because they decomposed more thoroughly meanwhile.…”
Section: Resultsmentioning
confidence: 99%
“…If the piezoelectricity is much larger than the electrostriction, its vibration will be increased by the repoling treatment for a normal piezoelectric ceramic. Previous studies have revealed that the electrostrictive vibration is larger than the piezoelectric vibration in MLCCs . Also, electrostrictive coefficients maintain the same sign regardless of the repoling treatment, because the sign of the strain caused by the electrostriction is independent of the polarity of the field.…”
Section: Repoling Methodsmentioning
confidence: 90%
“…By the late 2000s, problems concerning MLCC‐induced vibration and acoustic noise in electronic devices were well known. Only recently was the vibration of an MLCC attributed to the combined effects of piezoelectricity and electrostriction of the dielectric ceramic layers . With an alternating‐current (AC) electric field, the ceramic layers of the MLCC pulsate in the thickness direction, the vibration of which is transmitted to the circuit board through the solder joints.…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic refractory castables based on alumina (Al 2 O 3 ), spinel (MgOÁAl 2 O 3 ), and magnesia (MgO) as aggregates or matrix and calcium aluminate cement (CAC) as bond material are widely used in steel ladles and continuous casting tundishes because of their good slag resistance and spalling resistance. [1][2][3][4][5][6][7][8][9] After high temperature thermal treatment, the phases of these refractory castables consist of corundum (Al 2 O 3 ), spinel (MgOÁAl 2 O 3 ), and calcium hexa-aluminate (CaOÁ6Al 2 O 3 ) 9,10 It is well known that all the three phases possess high melting temperature and excellent high temperature properties. For instance, Al 2 O 3 with the melting point of 2050°C has the characteristics against oxidation and chemical corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 CaOÁ6Al 2 O 3 is thermodynamically stable up to its peritectic point around 1852 AE 7°C and exhibits a flexural strength and toughness comparable to alumina with similar porosity. 11,15 Therefore, it is desirable to obtain monolithic refractory castables with composition rich in Al 2 O 3 , MgOÁAl 2 O 3, and CaOÁ6Al 2 O 3 and to obtain such high temperature properties as good mechanical strength, thermal shock resistance, and slag penetration resistance.…”
Section: Introductionmentioning
confidence: 99%